Preparation method and precursor for improving the consistency of primary particles of positive electrode material precursor
By pausing feed, increasing rotation speed and introducing low-concentration salt and hydrogen peroxide solutions in the co-precipitation method, the problem of large differences in primary particles of the precursor of the positive electrode material of ternary lithium battery is solved, and the consistency and electrical performance of particles are achieved. Stablize.
Patent Information
- Application Number
- CN202411479460.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-10-23
AI Technical Summary
The prior art causes large differences in primary particle diameter width and diameter length when preparing the positive electrode material precursor of ternary lithium battery, which affects the consistency of electrical performance.
When preparing precursors by co-precipitation, when there are different particle sizes in the solution, all feeds are suspended and the rotation speed is increased to inhibit abnormal growth. Then, low-concentration salt solution and hydrogen peroxide solution are passed to guide the particles toward Grow in the same direction, reduce nucleation sites and improve particle consistency.
Through this method, the difference in diameter width and diameter length of primary particles can be significantly reduced, the particle uniformity and consistency of the precursor of the positive electrode material can be improved, and the electrical performance can be stabilized.
Smart Images

Figure CN118993177B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium battery materials, and in particular to a preparation method and a precursor for improving the consistency of primary particles of a positive electrode material precursor. Background Art
[0002] Ternary lithium batteries have become one of the mainstream application materials in the lithium battery market due to their high capacity, long life, and excellent high and low temperature cycles. The electrical properties of ternary material batteries are mainly determined by ternary precursors, which are usually co-precipitated with mixed salts, precipitants, and complexing agents at a certain temperature and pH, and are obtained through washing, drying, screening and other processes. The prepared precursors have certain differences in morphology and structure according to different series, indicators, and sizes. Among them, the primary particle stacking mode, diameter width, and diameter length have a greater impact on the electrical properties.
[0003] During the precursor preparation process, when there are process differences or the reaction system is adjusted frequently, the primary particle diameter width and length are prone to significant changes. Specifically, in the same particle, the primary particle diameter width difference is greater than 100nm, and the diameter length difference is greater than 200nm. This morphology structure is prone to overburning during the sintering process due to the obvious differences in primary particles, and the electrical properties of the obtained positive electrode material particles are different at each point, and the material consistency is poor, which in turn affects the overall performance. Summary of the invention
[0004] The purpose of the present invention is to overcome the defects of the above-mentioned prior art and to provide a preparation method and a precursor for improving the consistency of primary particles of a positive electrode material precursor.
[0005] The present invention solves the technical problem by adopting the following technical solutions.
[0006] The present invention provides a preparation method for improving the consistency of primary particles of a positive electrode material precursor, which comprises: when the positive electrode material precursor is prepared by a coprecipitation method, when primary particles of different sizes appear in a solution, all feedings are suspended, the rotation speed is increased to suppress abnormal growth of primary particles, and then a low-concentration salt solution and a hydrogen peroxide solution are introduced to guide the primary particles to grow in the same direction, reduce nucleation sites, and improve the consistency of the primary particles of the positive electrode material precursor.
[0007] The present invention provides a positive electrode material precursor, and the positive electrode material precursor is prepared by adopting the above method.
[0008] The present invention has the following beneficial effects:
[0009] The present invention provides a preparation method and precursor for improving the consistency of primary particles of a positive electrode material precursor. The present invention provides a preparation method for improving the consistency of primary particles of a positive electrode material precursor, which comprises: when the positive electrode material precursor is prepared by a coprecipitation method, when primary particles of different sizes appear in the solution, all feeds are suspended, the abnormal growth of primary particles is suppressed by increasing the rotation speed during the growth period, and then a low-concentration salt solution and a hydrogen peroxide solution are introduced to guide the primary particles to grow in the same direction, reduce nucleation sites, and ensure the consistency of the particles. The scheme provided by the present invention can be used to prepare a precursor with uniform primary particles, avoid the difference in primary particles caused by process adjustments or product characteristics, and stabilize the electrical properties of the positive electrode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0010] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0011] Figure 1 This is the SEM image of the product obtained in Example 1;
[0012] Figure 2 This is the SEM image of the product obtained in Example 2;
[0013] Figure 3 This is the SEM image of the product obtained in Comparative Example 1. DETAILED DESCRIPTION
[0014] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0015] The following is a detailed description of a preparation method and precursor for improving the consistency of primary particles of a positive electrode material precursor provided by an embodiment of the present invention.
[0016] In the first aspect, an embodiment of the present invention provides a preparation method for improving the consistency of primary particles of a positive electrode material precursor, which includes: when the positive electrode material precursor is prepared by a co-precipitation method, when primary particles of different sizes appear in the solution, all feeding is suspended, and then the rotation speed is increased to suppress the abnormal growth of the primary particles, and then a low concentration salt solution and a hydrogen peroxide solution are introduced to guide the primary particles to grow in the same direction, reduce nucleation sites, and improve the consistency of the primary particles of the positive electrode material precursor.
[0017] In the process of preparing the precursor, due to changes in the reaction system or the characteristics of the product itself, such as pH adjustment of the system or the introduction of a high flow of inert gas, primary particles of inconsistent sizes are easily formed. Obvious differences can be seen from the scanning electron microscope. The difference in the width of the primary particles is greater than 100nm, and the difference in the length is greater than 200nm. Due to the poor consistency of the primary particles, the performance of the positive electrode material or battery is reduced.
[0018] Therefore, the embodiment of the present invention provides a preparation method for improving the consistency of primary particles of positive electrode material precursors, which can avoid the problem of poor consistency of primary particles caused by the adjustment of process conditions. Under various process conditions, the number of nucleation sites on the surface of secondary spheres can be reduced, so that the difference in diameter width of the primary particles of the precursor is less than 20nm, and the difference in diameter length is less than 50nm, ensuring the uniformity and consistency of product particles and stabilizing the electrical performance of the product. The method is completed through physical adjustment and appropriate additives, without the need to add equipment, the method is simple, and is suitable for the preparation of a full range of precursors that have such problems.
[0019] In an optional embodiment, the steps include: under the protection of inert gas, flowing a mixed salt solution, a precipitant solution and a complexing agent solution into the bottom liquid in parallel, generating crystal nuclei and then lowering the pH of the system to grow primary particles; when primary particles of different sizes appear in the solution, suspending all feeding, increasing the rotation speed to suppress abnormal growth of primary particles, maintaining stirring speed; when precipitation tends to be suspended, introducing a low-concentration salt solution and a hydrogen peroxide solution of the same molar ratio to guide the primary particles to grow in the same direction, reduce nucleation sites, and improve the consistency of the primary particles of the positive electrode material precursor; when the diameter width and length differences meet the design requirements after re-feeding, the original feeding method is restored until the physicochemical indicators of the primary particles are qualified.
[0020] In an optional embodiment, the pH value of the reaction system is controlled to be 10.0-12.5. If the pH value is lower than the lower limit, the growth rate is too fast and the growth and size of the positive electrode material precursor particles cannot be controlled. If the pH value exceeds the upper limit, micropowder particles are likely to appear, making the reaction unable to proceed normally. The ammonia value is 2g / L-20g / L, and ammonia is adjusted with the pH change and is positively correlated. Mismatched ammonia values will affect the co-precipitation efficiency. The temperature is 40°C-80°C. If the temperature is lower than the lower limit, it is easy to cause a decrease in the mass transfer rate of the system and affect the crystallization of the particles. If the temperature exceeds the upper limit, it will cause oxidation of the precursor and affect the performance of the precursor. The rotation speed is 100rpm-1000rpm. If it is lower than the lower limit, the particles cannot be effectively dispersed and agglomerate severely, reducing the electrical properties of the precursor. If the temperature exceeds the upper limit, the particles in the system cannot be normally precipitated and crystallized, and the precursor cannot be synthesized.
[0021] In an optional embodiment, the pH of the system is lowered after the crystal nucleus is generated, and the reaction is continued for 5h-10h before the feeding is suspended. If the feeding is suspended for less than the specified time, the state of the reaction system will be inconsistent due to uneven mixing. If the feeding is suspended for more than the time, the particles will grow due to continuous feeding, causing the original crystal nucleus particle size to increase, affecting the regulation of the structure.
[0022] In an optional embodiment, the concentration of the mixed salt solution is 1.0 mol / L-2.5 mol / L, the mass concentration of the precipitant solution is 20%-25%, and the mass concentration of the complexing agent solution is 7%-30%. Liquid alkali (sodium hydroxide solution) is used as the precipitant and ammonia water is used as the complexing agent.
[0023] In an optional embodiment, the rotation speed is increased to 1.2 to 2 times the original rotation speed. By increasing the rotation speed, abnormal particle growth is suppressed, the particle size growth rate is slowed down, the particle size range of the affected particles is weakened, and high-speed stirring is used to change the crystallization state of the system. The pause time is maintained for 0.5h-10h to ensure that the crystallization state has been adjusted. Exceeding the time range will affect the continuity of particle growth and easily lead to single nucleation of the system.
[0024] In an optional embodiment, the concentration of the low-concentration salt solution is 0.3 to 0.8 times the concentration of the original mixed salt solution. The flow rate of the low-concentration salt solution can slow down its growth rate, allowing the particles to recrystallize in a uniform manner under the growth system.
[0025] In an optional embodiment, the mass fraction of the hydrogen peroxide solution is 5%-40%.
[0026] In an optional embodiment, the method further includes: aging and filtering the qualified reaction materials, slurrying the filter cake obtained by filtration with dilute alkali, filtering and washing until the pH value of the filtrate is less than 9, and obtaining a precursor product with uniform primary particles through drying, screening and demagnetization.
[0027] In a second aspect, an embodiment of the present invention provides a positive electrode material precursor, and the positive electrode material precursor is prepared by the above method.
[0028] As can be seen from the above, the embodiment of the present invention provides a preparation method for improving the consistency of primary particles of a positive electrode material precursor, which has the following characteristics and advantages:
[0029] (1) By adopting the solution provided in the embodiment of the present invention, a ternary precursor with uniform primary particles can be prepared, which can avoid the primary particle differences caused by process adjustment or product characteristics, and stabilize the electrical properties of the positive electrode material.
[0030] (2) The solution provided in the embodiment of the present invention is simple and effective, and no new elements are introduced, and is suitable for the preparation of a full range of NCM (lithium nickel cobalt manganese oxide, LiNiCoMnO2) and NCA (lithium nickel cobalt aluminum oxide, LiNiCoAlO2) precursors.
[0031] (3) The solution provided in the embodiment of the present invention can be applied to all stages of the precursor, specifically solving the problem of particle consistency, has no application taboos, and can be expanded to similar products such as quaternary precursors.
[0032] (4) The solution provided by the embodiment of the present invention has low application cost, excellent reaction control, and no need to modify existing equipment.
[0033] The present invention will be further described below in conjunction with the embodiments.
[0034] Example 1
[0035] The reactor bottom liquid was prepared with a temperature of 50°C, an ammonia value of 14 g / L, and a pH value of 11.4, and nickel-cobalt-manganese sulfate solution, ammonia water, and sodium hydroxide were simultaneously introduced into the reactor, and nitrogen was introduced for protection. The stirring speed of the reactor was set to 550 rpm, wherein the molar ratio of nickel-cobalt-manganese in the mixed salt solution was 6:1:3, the concentration of the mixed salt solution was 1.6 mol / L, the mass percentage concentration of the sodium hydroxide solution was 22%, and the mass percentage concentration of the ammonia water was 15%.
[0036] After the preparation of the crystal nucleus is completed, the pH value of the reaction system is adjusted to 10.9, the particles are in a growing state, and the reaction is continued for 8 hours before the feeding is suspended. The rotation speed is increased to 750 rpm, and the current process is maintained for 5 hours. Subsequently, a 0.8 mol / L salt solution of the same proportion is introduced, and a hydrogen peroxide solution with a mass fraction of 30% is introduced. During this period, electron microscopy monitoring is continuously performed. When the difference in diameter width and length meets the design requirements after re-feeding for 10 hours, the feeding process before suspension is restored until the physical and chemical indicators are qualified.
[0037] The kettle material is placed in an aging kettle for aging, then filtered, a certain concentration of dilute alkali is added to the filter cake for slurrying, and then filtered and washed until the pH value of the filtrate is less than 9, and then dried, sieved, and demagnetized to obtain a precursor material with uniform primary particles. Figure 1 It can be seen that the precursor particles are uniform and have good consistency.
[0038] Example 2
[0039] The reactor bottom liquid was prepared with a temperature of 45°C, an ammonia value of 6.5 g / L, and a pH value of 11.1, and nickel-cobalt-manganese sulfate solution, ammonia water, and sodium hydroxide were simultaneously introduced into the reactor, and nitrogen was introduced for protection. The stirring speed of the reactor was set to 360 rpm, wherein the molar ratio of nickel-cobalt-manganese in the mixed salt solution was 5:2:3, the concentration of the mixed salt solution was 1.6 mol / L, the mass percentage concentration of the sodium hydroxide solution was 22%, and the mass percentage concentration of the ammonia water was 15%.
[0040] After the preparation of the crystal nucleus is completed, the pH value of the reaction system is adjusted to 10.8, the particles are in a growing state, and the reaction is continued for 6 hours before the feeding is suspended. The rotation speed is increased to 504 rpm, and the current process is maintained for 8 hours. Subsequently, a 0.8 mol / L salt solution of the same proportion is introduced, and a hydrogen peroxide solution with a mass fraction of 30% is introduced. During this period, electron microscopy monitoring is continuously performed. When the difference in diameter width and length meets the design requirements after re-feeding for 6 hours, the feeding process before suspension is restored until the physical and chemical indicators are qualified.
[0041] The kettle material is placed in an aging kettle for aging, then filtered, a certain concentration of dilute alkali is added to the filter cake for slurrying, and then filtered and washed until the pH value of the filtrate is less than 9, and then dried, sieved, and demagnetized to obtain a precursor material with uniform primary particles. Figure 2 It can be seen that the precursor particles are uniform and have good consistency.
[0042] Comparative Example 1 (Compared with Example 1, this comparative example does not include speed adjustment, feeding suspension, low-concentration salt solution, and hydrogen peroxide solution)
[0043] The reactor bottom liquid was prepared with a temperature of 50°C, an ammonia value of 14 g / L, and a pH value of 11.4, and nickel-cobalt-manganese sulfate solution, ammonia water, and sodium hydroxide were simultaneously introduced into the reactor, and nitrogen was introduced for protection. The stirring speed of the reactor was set to 550 rpm, wherein the molar ratio of nickel-cobalt-manganese in the mixed salt solution was 6:1:3, the concentration of the mixed salt solution was 1.6 mol / L, the mass percentage concentration of the sodium hydroxide solution was 22%, and the mass percentage concentration of the ammonia water was 15%.
[0044] After the crystal nucleus preparation is completed, the pH value of the reaction system is adjusted to 10.9, the particles are in a growing state, and the current process is maintained to continuously feed, and the changes in the electron microscope morphology are monitored during the process until the physical and chemical indicators are qualified.
[0045] The kettle material is placed in an aging kettle for aging, and then filtered. A certain concentration of dilute alkali is added to the filter cake for slurrying, and then filtered and washed until the pH value of the filtrate is less than 9. The precursor material is obtained by drying, sieving, and demagnetization. The SEM of the precursor material is shown in Figure 3 It can be seen that the difference between the width and length of the primary particles of the prepared precursor is too large, which does not meet the design requirements.
[0046] Comparative Example 2 (Compared with Example 1, there is no speed adjustment in this comparative example)
[0047] The reactor bottom liquid was prepared with a temperature of 50°C, an ammonia value of 14 g / L, and a pH value of 11.4, and nickel-cobalt-manganese sulfate solution, ammonia water, and sodium hydroxide were simultaneously introduced into the reactor, and nitrogen was introduced for protection. The stirring speed of the reactor was set to 550 rpm, wherein the molar ratio of nickel-cobalt-manganese in the mixed salt solution was 6:1:3, the concentration of the mixed salt solution was 1.6 mol / L, the mass percentage concentration of the sodium hydroxide solution was 22%, and the mass percentage concentration of the ammonia water was 15%.
[0048] After the preparation of the crystal nucleus was completed, the pH value of the reaction system was adjusted to 10.9, the particles were in a growing state, and the reaction was continued for 8 hours before the feeding was suspended. The rotation speed was not increased, and then 0.8 mol / L salt solution of the same proportion was introduced, and a hydrogen peroxide solution with a mass fraction of 30% was introduced. During this period, electron microscopy monitoring was continuously performed. After 10 hours of re-feeding, the feeding process was restored to the state before suspension until the physical and chemical indicators were qualified.
[0049] The kettle material is placed in an aging kettle for aging, and then filtered. A certain concentration of dilute alkali is added to the filter cake for slurrying, and then filtered and washed until the pH value of the filtrate is less than 9. The precursor material is obtained through drying, screening, and demagnetization. Because the rotation speed is not adjusted, when primary particles of different sizes appear, the crystal state does not change significantly. When low-concentration salt solution and hydrogen peroxide solution are further used, it is not enough to change the uniformity of all particles in the system. Therefore, the difference in width and length of the prepared precursor primary particles is too large, which does not meet the design requirements.
[0050] Comparative Example 3 (Compared with Example 1, there is no holding time after the speed is increased in this comparative example)
[0051] The reactor bottom liquid was prepared with a temperature of 50°C, an ammonia value of 14 g / L, and a pH value of 11.4, and nickel-cobalt-manganese sulfate solution, ammonia water, and sodium hydroxide were simultaneously introduced into the reactor, and nitrogen was introduced for protection. The stirring speed of the reactor was set to 550 rpm, wherein the molar ratio of nickel-cobalt-manganese in the mixed salt solution was 6:1:3, the concentration of the mixed salt solution was 1.6 mol / L, the mass percentage concentration of the sodium hydroxide solution was 22%, and the mass percentage concentration of the ammonia water was 15%.
[0052] After the preparation of the crystal nucleus was completed, the pH value of the reaction system was adjusted to 10.9, the particles were in a growing state, and the reaction was continued for 8 hours before the feeding was suspended. The rotation speed was increased to 750 rpm without holding time, and then 0.8 mol / L salt solution of the same proportion was introduced, and a hydrogen peroxide solution with a mass fraction of 30% was introduced. During this period, electron microscopy monitoring was continuously carried out. When the feeding was resumed for 10 hours, the feeding process was restored to the state before the suspension until the physical and chemical indicators were qualified.
[0053] The kettle material is placed in an aging kettle for aging, then filtered, and the filter cake is added with a certain concentration of dilute alkali for slurrying, and then filtered and washed until the pH value of the filtrate is less than 9. The precursor material is obtained through drying, screening, and demagnetization. Since there is no holding time after increasing the speed, the crystal state does not change, and the subsequent process is not sufficient to make the primary particles grow uniformly. The difference in width and length of the prepared precursor primary particles is too large, which does not meet the design requirements.
[0054] Comparative Example 4 (Compared with Example 1, the concentration of the mixed salt solution in this comparative example was not adjusted)
[0055] The reactor bottom liquid was prepared with a temperature of 50°C, an ammonia value of 14 g / L, and a pH value of 11.4, and nickel-cobalt-manganese sulfate solution, ammonia water, and sodium hydroxide were simultaneously introduced into the reactor, and nitrogen was introduced for protection. The stirring speed of the reactor was set to 550 rpm, wherein the molar ratio of nickel-cobalt-manganese in the mixed salt solution was 6:1:3, the concentration of the mixed salt solution was 1.6 mol / L, the mass percentage concentration of the sodium hydroxide solution was 22%, and the mass percentage concentration of the ammonia water was 15%.
[0056] After the preparation of the crystal nucleus, the pH value of the reaction system was adjusted to 10.9, and the particles were in a growing state. After continuing the reaction for 8 hours, the feed was suspended, the speed was increased to 750rpm, and the current process was maintained for 5 hours. Then, a 1.6 mol / L salt solution of the same proportion was introduced, and a hydrogen peroxide solution with a mass fraction of 30% was introduced. During this period, electron microscopy monitoring was continuously performed. The diameter width and length of the primary particles did not improve. By comparison, the low-concentration salt solution played a role in continuously reducing the growth power of the reaction system during the crystal adjustment stage, and at the same time provided the system with the raw materials and time required for crystal transformation. After increasing the speed, if the original concentration mixed salt solution is used, the growth power will be maintained at a high level, and its growth rate cannot be effectively reduced. The abnormal particles continue to grow abnormally due to their power, and the diameter width difference of the final product is greater than 20nm, which does not meet the design requirements.
[0057] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for improving the consistency of primary particles of a positive electrode material precursor, characterized in that: The method comprises: when the cathode material precursor is prepared by the coprecipitation method, when the primary particles of different sizes appear in the solution, all feeding is suspended, and then the rotation speed is increased to suppress the abnormal growth of the primary particles, and then a low-concentration salt solution and a hydrogen peroxide solution are introduced to guide the primary particles to grow in the same direction, reduce the nucleation sites, and improve the consistency of the primary particles of the cathode material precursor, wherein: the concentration of the low-concentration salt solution is 0.3 times to 0.8 times the concentration of the original mixed salt solution, and the rotation speed is increased to 1.2 times to 2 times the original rotation speed, and the pause time is maintained for 0.5h to 10h.
2. The preparation method according to claim 1, characterized in that: The following steps are involved: Under the protection of inert gas, a mixed salt solution, a precipitant solution and a complexing agent solution are introduced into the bottom liquid in parallel. After the crystal nucleus is generated, the pH of the system is lowered to grow the primary particles. When the primary particles of different sizes appear in the solution, all feedings are suspended, and the rotation speed is increased to suppress the abnormal growth of the primary particles. The stirring speed is maintained. When the precipitation tends to be suspended, a low-concentration salt solution and a hydrogen peroxide solution with the same molar ratio are introduced to guide the primary particles to grow in the same direction, reduce the nucleation sites, and improve the consistency of the primary particles of the positive electrode material precursor. When the difference in diameter width and length meets the design requirements after re-feeding, the original feeding method is restored until the physicochemical indicators of the primary particles are qualified.
3. The preparation method according to claim 2, characterized in that: The pH value of the reaction system is controlled to be 10.0-12.5, the ammonia value is 2g / L-20g / L, the temperature is 40°C-80°C, and the rotation speed is 100rpm-1000rpm.
4. The preparation method according to claim 2, characterized in that: After the crystal nucleus is generated, the pH of the system is lowered, and the reaction is continued for 5h-10h before the feed is suspended.
5. The preparation method according to claim 2, characterized in that: The concentration of the mixed salt solution is 1.0 mol / L-2.5 mol / L, the mass concentration of the precipitant solution is 20%-25%, and the mass concentration of the complexing agent solution is 7%-30%.
6. The preparation method according to claim 2, characterized in that: The mass fraction of the hydrogen peroxide solution is 5%-40%.
7. The preparation method according to claim 2, characterized in that: Also includes: The qualified reaction materials are aged and filtered, the filter cake obtained by filtration is slurried with dilute alkali, filtered and washed until the pH value of the filtrate is less than 9, and then dried, sieved and demagnetized to obtain a precursor product with uniform primary particles.
8. A positive electrode material precursor, characterized in that: The positive electrode material precursor is prepared by the method according to any one of claims 1 to 7.
Citation Information
Patent Citations
Ternary positive electrode material precursor and preparation method thereof
CN116062803A
Ternary precursor and preparation method thereof, lithium battery positive electrode material and lithium battery
CN116588993A